The Impact of Social Support Networks on Family Resilience in an Australian Intensive Care Unit: A Constructivist Grounded Theory. Issue 1 (23rd November 2018) - Wong, Pauline; Liamputtong, Pranee; Koch, Susan; Rawson, Helen
Abstract: Purpose: This article discusses the findings of a grounded theory of family resilience in an Australian intensive care unit (ICU) with a specific focus on families' experiences of their interactions with other members within their own family, and the families of other patients in the ICU. Design: A constructivist grounded theory methodology was adopted. Data were collected using in‐depth interviews with 25 family members of 21 critically ill patients admitted to a tertiary‐level ICU in Australia. Findings: The core category regaining control represents the families' journey toward resilience when in ICU. The major categories represent facilitators for, and barriers to, regaining control. One of the main facilitators is drawing strength, and it explains the manner with which families receive social support from their own and other family members to help them cope. Conclusions: This study offers a framework to improve patient‐ and family‐centered care in the ICU by facilitating families' ability to manage their situation more effectively. Social support offered by family members facilitates the families' ability to regain control. An ICU family resilience theoretical framework, situated within the context of the Australian healthcare system, adds to what is currently known about the families' experiences in the ICU. Clinical Relevance: The relationships that develop between families in the ICU may provide a source of social support; however, not all families welcome interactions with other ICU families, and it may cause further emotional distress. Further research is warranted to determine whether families suffer a secondary stress reaction from incidental interactions with other patients' families in the ICU. Furthermore, when family members pull together and offer social support to each other, they are better able to regain control. This process contributes to an ICU family resilience framework.